PERENCANAAN PROGRAM SEKOLAH PENGGERAK DENGAN BERBASIS DATA DI SD NEGERI GEDANGANAK 02 - Qun Firmani Lestari; Ardhina Maya Nugraheni; Haniatul Mas’udah; Ayu Rosydina; Ngurah Ayu Nyoman M (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to analyze the planning of the driving school program using SWOT analysis to help improve the quality of education at Gedanganak 02 State Elementary School. This research uses qualitative methods, meaning the researcher conducted interviews, directly observed activities at the school, and collected various documents. The results show that the school program planning carried out by Gedanganak 02 State Elementary School refers to the school's vision, mission and goals. However, it does not rule out the possibility of planning the school program also referring to the results of the education report that was carried out during the Computer Based National Assessment (ANBK) in the previous period. Planning is very important in preparing school programs. School programs must be created in line with the school's vision, mission and goals. This is a privilege for an educational institution to be superior and stand out from other schools. Gedanganak 02 State Elementary School has the key to this secret, namely the existence of superior activities or programs which have been the favorites of entrepreneurship-based schools such as Hydroponics, Budikdamber (Cultivating fish in buckets), Project P5 Activities, and Extracurricular Activities. In data-based planning sourced from education reports, schools can utilize data to understand the strengths and weaknesses of each student.